Evaluation of the anticonvulsant effect of nimodipine and amlodipine in mice using maximal electroshock test - Shankpal, Pramod D.; Tawte, Priyanka M. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Initial stage of seizure is due to high frequency burst of action potential, caused by long lasting depolarization of the neuronal membrane because of large influx of calcium (Ca) ions into cells. As there is role of calcium channels in the initiation of seizure potential, there may be role of calcium channel antagonists in treatment of epilepsy. Therefore, we assessed the anticonvulsant effect of nimodipine and amlodipine in mice and compared it with phenytoin and sodium valproate. Methods: A total 42 mice were randomly divided into 7 groups with 6 mice each. Group 1 vehicle (1% CMC), group 2- phenytoin (25 mg/kg) and group 3- sodium valproate (100 mg/kg) p.o. group 4 and 5- nimodipine (4 mg/kg and 8 mg/kg), group 6 and 7- amlodipine (0.7 mg/kg and 1.3 mg/kg) p.o. in 1% CMC. All animals were tested for convulsions with current strength 50 mA for 0.2 seconds, delivered by ear electrodes of electroconvulsiometer. Parameters assessed were presence or absence of convulsions, onset of (latency to) THLE and duration of THLE in seconds, 24 hours mortality. Results: The difference in percentage of mice being protected from electro convulsions was found to be statistically significant in group 5 (nimodipine 8 mg/kg), group 7 (amlodipine 1.3 mg/kg) as compared to group 1(vehicle control) (p= 0.0152). Onset of (latency to) THLE and duration of THLE, expressed as mean (in seconds) ± standard deviation (SD) and analysed using Kruskal-Wallis non-parametric test showed significant difference in latency to THLE among the groups tested (p value <0.01) and in duration of THLE among the groups tested (p value <0.01), while post- hoc Dunn’s test showed a statistically significant difference between latency to and duration of THLE in the nimodipine 8 mg/kg and amlodipine 1.3 mg/kg groups as compared to vehicle control group (p<0.01). No mortality seen within 24 hours of testing in any group. Conclusions: Nimodipine 8 mg/kg and amlodipine 1.3 mg/kg showed significant anticonvulsant activity (absence of tonic hind limb extension), delayed onset of seizures, reduced duration of seizures comparable to positive control (phenytoin and sodium valproate) and more effective than vehicle control.